Activities of Liquid Organic Fertilizer from the Date Juice Waste During Hydroponic Plant Growth (Indonesian Journal of Chemical Science, 2022)
PT. Herba Emas Wahidatama (Purbalingga) has date palm juice waste as a result of date palm juice that has not been standardized and has expired. Dates juice waste is used as liquid organic fertilizer so that it can be resold and produces less waste residue. This study aims to determine the effect of variations in EM4 volume and fermentation time on levels of C-organic, nitrogen, phosphorus, and potassium liquid organic fertilizer and determine the results of liquid organic fertilizer application on hydroponic plant growth. The method of preparation of liquid organic fertilizer uses a fermentation process with a volume variation of the bio activator EM4 0; 20; 40 mL and fermentation time 7; 14; 21 days. Liquid organic fertilizer analysis methods include the Walkley and Black method (C-organic), Kjeldahl (N-total), spectrophotometry (P-total), and atomic absorption spectrophotometer (K-total). The yield of C-organic content is 25.00-30.43%, nitrogen content is 0.01-0.18%, phosphorus is 0.05-0.09%, potassium is 0.34-0.71%, pH is 4.26– 4.41. With more volume of EM4, organic C- and phosphorus levels increased, and nitrogen and potassium levels decreased. The longer the fermentation time, the C-organic content increased, the nitrogen and phosphorus content decreased, and the potassium level increased and then decreased. The results of the application of liquid organic fertilizer on water spinach plants using the hydroponic wick system did not grow after 10 days of sowing, the plants lasted a week and then withered and died. This is due to more C-Organic than the levels of nitrogen, phosphorus, potassium, and lack of sunlight for photosynthesis so plants experience etiolation symptoms.